Performance Issues for Parallel Implementations of Bootstrap Simulation Algorithm - Czekster, Ricardo M.; Fernandes, Paulo; Sales, Afonso; Webber, Thais (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2010: Anais do XXII International Symposium on Computer Architecture and High Performance Computing, 2010)
The solution of state-based stochastic models is usually a demanding application, then it is a natural subject to high performance techniques. We are particularly interested in the speedup of Bootstrap Simulation of structured Markovian models. This approach is a quite recent development in the performance evaluation area, and it brings a considerable improvement in the results accuracy, despite the intrinsic effect of randomness in simulation experiments. Unfortunately, Bootstrap Simulation has higher computational cost than other alternatives. We present experiments with different options to optimize the parallel solution of Bootstrap Simulation applied to three practical examples described in Stochastic Automata Networks (SAN) formalism. This paper contribution resides in the discussion of theoretical implementation issues, the obtained speedup and the actual processing and communication times for all experiments. Additionally, we also suggest future works to improve even more the proposed solution and we discuss some interesting insights for parallelization of similar applications.